Pembuatan dan Uji Sifat Fisikokimia Pati Beras Ketan Kampar yang Dipragelatinasi - Lukman, Anita; Anggraini, Deni; Rahmawati, Noveri; Suhaeni, Nani (Jurnal Penelitian Farmasi Indonesia, 2013)
Glutinous rice contains 99.7% of amilopectin. The amilopectin does not swell in cold water and it could retard the desintegration anddissolution of drug. Physical modification of glutinous rice by pregelatization can enhance the swelling power of starch in cold water. In thisstudy, glutinous rice used as sample was collected from three difference places which are kecamatan Air Tiris, Rumbio Jaya dan Salo kabupatenKampar, Riau province. Sample was subjected to pregelatization process manually as well as by using Spray Dryer. The result showed thatpregelatized glutinous rice starch gave the higher swelling power than glutinous rice. Glutinous rice from Rumbio Jaya showed the highestswelling power of 343.87%. This value indicated that it could be potential candidate as sustained release agent.